Treatment of lipomas and diffuse lipomatosis with NDYAG 1064 NM laser and their impact on the quality of life - Valeriu Ardeleanu; Liliana Florina Andronache; Florentina Gherghiceanu; Stana Paunica; Cristian Balalau; Anca Pantea Stoian (Journal of Mind and Medical Sciences)
Lipomas, the most common type of benign tumours, are generally developed from adipose tissue and present an incidence of 2.1 per 1000 inhabitants. In addition to lipomas, at least three other maladies of the adipose tissue lead patients to consult a doctor, especially for aesthetic purposes: multiple familial lipomatosis, diffuse congenital lipomatosis, and adiposa doloris. Unlike lipomas, these maladies are characterized by numerous lipomas, encapsulated or not, of different sizes, symmetrical or not, which may appear in the neck, limbs, or the trunk, sometimes being painful. The life quality of these patients is affected, not only from an aesthetic point of view but also from medical considerations, like pain. Chemical lipolysis has proven unsatisfactory for patients due to several reasons: the prolonged therapy, high cost, the partial dissolution of the lipomatosis, and high recurrence at one year. Surgical treatment remains the only viable option; sometimes when numerous lipomatous tumors required large and numerous incisions, treatment was refused by patients. The result after laser liposuction is excellent, the recovery time is short, without much pain for the patient, with minimal ecchymoses and edemas, without any recurrence in time, and with an excellent degree of patient satisfaction.